Land Use Change Impact on Erosion and Sedimentation in Kreo Sub-Watershed, Central Java - Napitupulu, Ruth Erditha; Andawayanti, Ussy; Bisri, Mohammad; Putra, Rizky Almarendra Wirawan (Universitas Diponegoro, 2025)
Ministry of Forestry has designated Kreo Sub-watershed, part of Garang Watershed, a critical area due to high erosion rates contributing to flooding in Semarang. Rapid land use changes accelerate environmental degradation, increasing erosion and sedimentation risks. This study measures erosion and sedimentation rates in Kreo Sub-watershed using SWAT (Soil and Water Assessment Tool), determines Erosion Hazard Index, and proposes erosion control solutions based on Land Rehabilitation and Soil Conservation Analysis (ARLKT) with vegetative conservation. ARLKT approach includes simulating new land use scenarios to assess their impact on erosion reduction. To ensure SWAT modelling accurately represents field conditions and not overestimate, allowing conservation recommendations based on ARLKT applied appropriately, a field-based sedimentation analysis also conducted. The study utilizes rainfall, soil type, slope, and land use data in 2019 and 2024 from satellite imagery and validated using a confusion matrix. Results indicate a shift in Erosion Hazard Index from predominantly ‘Moderate’ in 2019 to ‘High’ in 2024, underscoring urgent need for sustainable watershed management. By integrating remote sensing, field validation, and hydrological modeling, this study offers a precise, data-driven approach to erosion control. The findings serve critical reference for policymakers in developing effective conservation strategies to enhance watershed resilience.